Psychological safety and its relationship to smartphone use addiction among high school students in Jazan educational administration - Hakamy, Amani Mohammad Abdo; Al-Sharjabi, Ikhlas Abdul Raqib Salam (Journal of Educational and Psychological Sciences, 2021)
The study aimed to discover the relationship between psychological safety and smartphone among high school students in the Jazan Educational administration and to predict smartphone use addiction through the psychological safety among high school students in the Jazan Educational administration. and the researcher used the relational-descriptive method, and the Psychological Safety Scale was used by (Shukair: 2005), and smartphone Addiction Scale by (Alosaimai et, al.: 2016).The study sample consisted of (430) female students from the secondary stage of the Jazan Educational administration, they were randomly selected from the three general secondary grades of the schools affiliated to Jazan Educational Administration Where the arithmetic mean of their ages (16.074), The results indicated the high level of psychological safety among the study sample of high school students, and the high level of smartphone use addiction among secondary school students. It also indicated that there is a negative correlation between psychological safety and smartphone use addiction among secondary school students at the significance level (0.01), and the possibility of predicting smartphone use addiction among secondary school students through the dimensions of psychological safety at the level of significance (0.01) through each degree of (the individual mood, the individual composition, and his vision for the future). The study recommends educating mothers and fathers about the correct educational methods in dealing with cases of children’s smartphone addiction.